The value and role of food labels: three essays examining information flows in the food system for experience and credence attributes - Deselnicu, Oana C., author; Costanigro, Marco, advisor; Thilmany-McFadden, Dawn, advisor; Kroll, Stephan, committee member; Manning, Kenneth, committee member (Colorado State University. Libraries, 2012)
This dissertation investigates the role of food labels as means of conveying information about food product characteristics, with particular attention to experience and credence attributes. Unobserved product characteristics such as taste, food safety, nutrition, or quality are inherently difficult to quantify but are frequent determinants of demand. Since not all these characteristics are measurable (e.g., food safety) or directly observable (e.g., nutrition), there exists information asymmetry in the market between firms and consumers. Product labeling is a way for information that is initially hidden to eventually be disseminated in the marketplace. Different labeling schemes serve different roles in the marketing system. For example, nutrition information is critical in consumption decisions, while other product characteristics (such as "organic", or "fair trade"), may be valued by consumers but not essential for decision-making. Across three essays, we provide an assessment of how different types of labels are used in the food system. We focus equally on labels that have a long and rich history of usage in the food system (such as nutrition labels, and more recently, geographical indication (GI) labeling which denote a relationship between the product origin and specific product characteristics), but also labels that address emerging, public-minded issues which may be increasingly relevant in the future (such as environmental impact labeling and Corporate Social Responsibility (CSR) labeling). First, we meta-analyzed the literature regarding GI valuation to generate a set of guidelines, independent of any particular study, outlining the factors that are instrumental for a GI product to capture a price premium. Our findings across many studies indicate that agricultural produce and minimally processed foods such as grains, fresh meats, fruits and vegetables, benefit the most from association with GIs. These product categories generally do not develop own private reputations (brands), and thus, the premia received from association with GI collective reputations is relatively high. On the other hand, in addition to GIs, products with high value-added and longer supply chains such as wines and olive oils may also use private brands more effectively for differentiation. This suggests that brands and GIs have at least a partial substitute relationship. So, as the most broadly framed of the studies here, this cross-sectional analysis would suggest a further exploration of targeted labeling strategies, used jointly or independently of specific brand-name products, is warranted. Next, using original survey data and looking at nutrition label information, we find that truncated nutrition searches (looking only at the front label), or misleading product claims (such as "organic") are among a broad set of reasons current nutrition labeling practices may be ineffective in uniformly conveying information to consumers. We find that a nutrition index summarizing the information on the back nutrition panel, coupled with the information on the front label, may help to mitigate the incomplete information problems presented above. Moreover, we find that the environmental impact of food production is hard to identify by consumers if there is a lack of proper certification. But, until more consensus about key outcomes is framed by relevant government or consumer-oriented NGOs, a similar "informational index" solution will not be possible, so policy options are more limited. Finally, using original survey data we identify consumer preferences for CSR actions in the dairy industry. We find animal welfare to be the most preferred CSR activity and a top priority for most consumers. Sustainable agricultural practices, energy consumption, and waste management are second, third, and fourth, respectively, in importance for consumers; while company involvement in the community has the lowest priority amongst consumers. Furthermore, we monetize the value of animal welfare claims, identified as the most important CSR activity by consumers, in the context of a trusted third-party certification such as the Validus animal welfare certification program. Together, these empirical analyses provide a diverse set of findings on consumer perceptions, use of information, part-worth valuation of specific characteristics, as well as how these findings may vary by segments of consumers and product categories. By exploring these issues from a variety of perspectives and methods, the studies make both market-relevant and methodological contributions to the food labeling field.